2018
DOI: 10.1111/plb.12865
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term cadmium exposure influences the abundance of proteins that impact the cell wall structure in Medicago sativa stems

Abstract: Cadmium (Cd) is a non‐essential, toxic heavy metal that poses serious threats to both ecosystems and human health. Plants employ various cellular and molecular mechanisms to minimise the impact of Cd toxicity and cell walls function as a defensive barrier during Cd exposure.In this study, we adopted a quantitative gel‐based proteomic approach (two‐dimensional difference gel electrophoresis) to investigate changes in the abundance of cell wall and soluble proteins in stems of Medicago sativa L. upon long‐term e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 98 publications
7
42
0
1
Order By: Relevance
“…Our MS data do not confirm that the inhibitor domain is cut from the PME domain. However, the position on the 2D gel matches with what is predicted for the active protein and are at the same position as those found in M. sativa stems [ 30 ]. In the latter study, cleavage between the inhibitor and the active domain was confirmed based on MS data, indicating that in leaves the inhibitor domain was also cleaved and thus the protein activated.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Our MS data do not confirm that the inhibitor domain is cut from the PME domain. However, the position on the 2D gel matches with what is predicted for the active protein and are at the same position as those found in M. sativa stems [ 30 ]. In the latter study, cleavage between the inhibitor and the active domain was confirmed based on MS data, indicating that in leaves the inhibitor domain was also cleaved and thus the protein activated.…”
Section: Discussionsupporting
confidence: 76%
“…Identified proteins were clustered according to their biological function using Blast2Go ( Figure 2 ) and those assignments as well as the number of proteins showing an increased or decreased abundance upon Cd exposure are comparable with results from a similar study on M. sativa stems [ 30 ]. In both studies, results confirm that the enrichment obtained with the used protocol is better than that obtained with comparable protocols, but not 100% and several non-apoplastic proteins, mainly chloroplast targeted, were identified most prominent in the CaCl 2 fraction ( Figure 2 ) [ 30 ]. Those proteins will also be discussed as they are highly abundant in leaves and coherent, significant changes in abundance were observed between replicates and fractions in response to Cd exposure.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Cadmium pollution has expanded rapidly in the last hundred years through human activities, such as mining, waste emissions, and fertilizer abuse. Cadmium stress not only affects herbage yield, cell wall structure, and lignification but also poses serious health risks to animals and humans by enrichment through food chains [39]. Previous research has shown the important role of redox status in H 2 -enhanced Cd tolerance and decreased Cd uptake in alfalfa, but little is known about the relative mechanisms involved [27].…”
Section: Introductionmentioning
confidence: 99%